Pengembangan Modul Bilingual Bergambar Berbasis Quantum Learning pada Materi Peluang - Sandiyanti, Ageng; Rakhmawati M, Rosida (Universitas Islam Negeri Raden Intan Lampung, 2018)
This study aims to produce products in the form of bilingual module based on quantum learning on the material opportunities. This research includes the type of research and development (Research and Development) refers to a model consisting of five steps of activities namely analysis, design, development, implementation, and evaluation. The result of the research shows that the module that obtained the average percentage value from the material expert is 83,33% with the very good criterion, the average percentage value from media expert is 85% with very good criteria and the average percentage value from the linguist ie 78.67% with very good criteria. The bilingual module based on quantum learning on the opportunity meters also obtained a percentage value of 80% student response with very good criteria and obtained the percentage value of educator equal to 84% with very good criteria.